Rozwijanie świadomości i wrażliwości kulturowej na warsztatach translatorskich z języka włoskiego na przykładzie podręcznika akademickiego Utile e traducibile. Esercizi di lessico settoriale e quotidiano - Kowalik, Katarzyna; Woch, Agnieszka (Neofilolog, 2023)
The aim of the article is to describe our proposition of method of developing sensitivity to different cultures, and in particular cultural and intercultural competence during Italian translation workshops. It discusses the content of higher education books for teaching functional languages. The authors pay special attention to the selection of appropriate authentic texts and real-life curiosities that go beyond the basic messages conveyed during courses and in the textbooks. In the analysed university script, one can find texts about atypical historical, linguistic, literary, and cinematic references or about surprising common points that allow the learner to relate to Polish and even to his or her local context. The authors share their reflections on the reception of the book by students.